Hydrological behavior and drought analysis in the Pandeiros river basin, Brazilian savanna - Junqueira, Rubens (2022)
Hydrological studies are important to assist the water resources management in watersheds, especially in the face of extreme events such as droughts. However, the availability of hydrometeorological observed data in Brazil is low, besides presenting several problems, such as gaps in historical series and irregular spatial distribution. Therefore, this study aimed to (i) analyze the characteristics and propagation of meteorological to hydrological drought and its influence on hydrological behavior in the Pandeiros river basin (PRB), located in the Cerrado biome; ii) to validate precipitation using Tropical Rainfall Measuring Mission Multi-Satellite Precipitation Analysis (TMPA) and Integrated Multi-satellitE Retrievals for Global Precipitation Measurement (IMERG) data, as well as to evaluate the performance and uncertainty of hydrological modeling with these data and with observed precipitation; and iii) to perform hydrological retrospective (RH) using climate reanalysis data and to analyze the occurrence and characteristics of historical droughts in the basin. For this, observed hydrometeorological data, climate data from the Climatic Research Unit (CRU), satellite-based estimated rainfall data (TMPA and from IMERG), and climate reanalysis (20th-century atmospheric model ensemble - ERA-20CM, and the land component of the 5th generation European ReAnalysis - ERA5-Land) were used. In addition, the Digital Elevation Model and maps of land type and land use were used. Hydrological modeling was performed with the Soil and Water Assessment Tool (SWAT). Standardized Precipitation Index (SPI) and Standardized Streamflow Index (SSI) were also used to determine meteorological and hydrological droughts, respectively. In the drought propagation analysis, the meteorological drought caused a reduction in groundwater recharge, generating the occurrence of hydrological drought even after the normalization of precipitation. The drought propagation presented a higher correlation for a lag of up to six months of the SPI in relation to the SSI, and for longer lags, a lower influence of the meteorological drought on the hydrological one was observed. With respect to the analysis of satellite precipitation products, both IMERG and TMPA overestimated the observed precipitation. IMERG showed better performance in validating the precipitation and streamflow simulated with the hydrological model and is considered an important alternative for hydrological studies in the BHRP. Among the climate reanalysis products, ERA5-Land showed satisfactory results in estimating precipitation, streamflow simulated with the hydrological model, and hydrological drought in the basin, while the products derived from ERA-20CM showed unsatisfactory performance in all analyses. Thus, ERA5-Land was used to perform hydrological reanalysis from 1950 to 2018, as well as analyze the occurrence and characteristics of historical hydrological droughts in the basin, where it was possible to identify that the years 1958/62, 1970/72, 1974/77, 2001/03, and 2012/18 were those with the greatest drought severity and duration in the analyzed period. In addition, an increase in the number of drought months and a reduction of wet months was observed in the last decades, with 51.7% of the dry months occurring from 1996 on. Therefore, ERA5-Land is suitable for hydrological studies involving long historical series in the basin.